Developing the WBS-Based Standard Operating Procedure of Highrise Building’s Architectural Components - Putritama, Dewini; Riantini, Leni Sagita; Machfudiyanto, Rossy Armyn (Interdisciplinary Social Studies, 2022)
The maintenance of the building should have clear and planned standards. In compiling standard operating procedures for maintenance and care, people can use the Work Breakdown Structure (WBS) to make it easier to understand by grouping each component of the building and being oriented towards overall activities. The purpose of this study is to find out the variables in developing SOPs for maintenance and care of architectural components in office buildings. The method used is literature study and expert validation. The research strategy was archival analysis in the form of previous project documents and government regulations related to maintenance and care as well as surveys to experts to validate variables. The research instrument used is a Questionnaire. Furthermore, the questionnaire data were analyzed using descriptive statistics which then produced SOP development variables. The results of the study are expected to be a reference SOP for building managers in carrying out building maintenance and care.